Pengaruh Experiential Marketing, Citra Perusahaan Dan Kualitas Produk Terhadap Kepuasan Konsumen Pada Pt. Pos Indonesia (Persero) Kota Probolinggo - Mahmuda, Nur Amilia; Hendra, Joni; Hermawan, Dedi Joko (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
The study aims to determine the effect of Experiential Marketing, Company Image and Product Quality on Customer Satisfaction at PT Pos Indonesia (Persero) Probolinggo City. The research method used is a quantitative approach, with variables consisting of independent variables, namely Experiential Marketing, Company Image and Product Quality and the dependent variable, namely Customer Satisfaction. The population in this study were all consumers at PT Pos Indonesia (Persero) Probolinggo City and the sample used amounted to 100 respondents based on certain criteria, namely consumers who have made transactions at PT Pos Indonesia (Persero) Probolinggo City. The data sources used in this study come from primary data and secondary data, with the help of the PLS 3 application. The results showed that the Experiential Marketing variable (X1) had no effect on Consumer Satisfaction (Y) of (-0.015) with t statistic (1.107 < 1.96) or p value (0.457 > 0.05) and the Company Image Variable (X2) had no effect on Consumer Satisfaction (Y) of (0.250) with t statistic (3.786 > 1.96) or p value (0.216 < 0.05). While the Product Quality Variable (X3) has an effect on Customer Satisfaction (Y) of (0.864) with t statistic (2.801> 1.96) or p value (0.003 <0.05), it is proven that the hypothesis is accepted on the Product Quality variable has a significant effect on Customer Satisfaction at PT. Pos Indonesia (Persero) Probolinggo City.